Drugs and life-threatening ventricular arrhythmia risk: results from the DARE study cohort. Issue 10 (16th October 2017) - Coughtrie, Abigail L; Behr, Elijah R; Layton, Deborah; Marshall, Vanessa; Camm, A John; Shakir, Saad A W
Abstract : Objectives: To establish a unique sample of proarrhythmia cases, determine the characteristics of cases and estimate the contribution of individual drugs to the incidence of proarrhythmia within these cases. Setting: Suspected proarrhythmia cases were referred by cardiologists across England between 2003 and 2011. Information on demography, symptoms, prior medical and drug histories and data from hospital notes were collected. Participants: Two expert cardiologists reviewed data for 293 referred cases: 130 were included. Inclusion criteria were new onset or exacerbation of pre-existing ventricular arrhythmias, QTc >500 ms, QTc >450 ms (men) or >470 ms (women) with cardiac syncope, all secondary to drug administration. Exclusion criteria were acute ischaemia and ischaemic polymorphic ventricular tachycardia at presentation, structural heart disease, consent withdrawn or deceased prior to study. Descriptive analysis of Caucasian cases (95% of included cases, n=124) and culpable drug exposures was performed. Results: Of the 124 Caucasian cases, 95 (77%) were QTc interval prolongation-related; mean age was 62 years (SD 15), and 63% were female. Cardiovascular comorbidities included hypertension (53%) and patient-reported 'heart rhythm problems' (73%). Family history of sudden death (36%) and hypokalaemia at presentation (27%) were common. 165 culpable drug exposures were reported, including antiarrhythmics (42%), of which amiodarone and flecainide were the most common. Sotalol, a beta-blocking agent with antiarrhythmic activity, was also common (15%). 26% reported multiple drugs, of which 84% reported at least one cytochrome (CYP) P450 inhibitor. Potential pharmacodynamics interactions identified were mainly QT prolongation (59%). Conclusions: Antiarrhythmics, non-cardiac drugs and drug combinations were found to be culpable in a large cohort of 124 clinically validated proarrhythmia cases. Potential clinical factors that may warn the prescriber of potential proarrhythmia include older women, underlying cardiovascular comorbidity, family history of sudden death and hypokalaemia.